Near-lethal self-harm in women prisoners: contributing factors and psychological processes - Marzano, L; Fazel, S; Rivlin, A; Hawton, K (2011)
We investigated the circumstances and psychological processes involved in the near-lethal self-harm acts of 60 women prisoners, using qualitative and quantitative methods. Most incidents involved hanging or ligaturing and high levels of suicidal ideation, and were attributable to individual and prison-related factors. Half of the incidents were described as impulsive, but mostly occurred against a background of longer-term suicidality and multiple repeated attempts. Hopelessness and images of past trauma were common in the lead-up to the acts. These findings have implications for prevention of suicidal behaviour in female prisoners. © 2011 Copyright Taylor and Francis Group, LLC.